Survey of Mental Health Professionals’ Knowledge and Skills in Managing Substance Misuse in Patients Admitted on a Mental Health High Dependency Unit - Heba Salem; Nidhi Gupta (BJPsych Open)
Aims: Dual diagnosis is very common in patients who have a psychotic disorder. This impacts symptom severity, treatment outcomes, and relapse rates. Following multiple incidents of drug misuse on a high dependency unit and inconsistent staff approach in dealing with these issues, we recognized the need to assess staff knowledge as a first step toward providing effective patient care. The aim of this survey was to assess knowledge and skills of mental health professionals to manage patients who misused substances while being admitted to a high dependency unit.